RNA-Seq reveals infection-induced gene expression changes in the snail intermediate host of the carcinogenic liver fluke, Opisthorchis viverrini. - Sattrachai Prasopdee; Javier Sotillo; Smarn Tesana; Thewarach Laha; Jutharat Kulsantiwong; Matthew J Nolan; Alex Loukas; Cinzia Cantacessi (PLoS Neglected Tropical Diseases, 2014)
Background Bithynia siamensis goniomphalos is the snail intermediate host of the liver fluke, Opisthorchis viverrini, the leading cause of cholangiocarcinoma (CCA) in the Greater Mekong sub-region of Thailand. Despite the severe public health impact of Opisthorchis-induced CCA, knowledge of the molecular interactions occurring between the parasite and its snail intermediate host is scant. The examination of differences in gene expression profiling between uninfected and O. viverrini-infected B. siamensis goniomphalos could provide clues on fundamental pathways involved in the regulation of snail-parasite interplay. Methodology/principal findings Using high-throughput (Illumina) sequencing and extensive bioinformatic analyses, we characterized the transcriptomes of uninfected and O. viverrini-infected B. siamensis goniomphalos. Comparative analyses of gene expression profiling allowed the identification of 7,655 differentially expressed genes (DEGs), associated to 43 distinct biological pathways, including pathways associated with immune defense mechanisms against parasites. Amongst the DEGs with immune functions, transcripts encoding distinct proteases displayed the highest down-regulation in Bithynia specimens infected by O. viverrini; conversely, transcription of genes encoding heat-shock proteins and actins was significantly up-regulated in parasite-infected snails when compared to the uninfected counterparts. Conclusions/significance The present study lays the foundation for functional studies of genes and gene products potentially involved in immune-molecular mechanisms implicated in the ability of the parasite to successfully colonize its snail intermediate host. The annotated dataset provided herein represents a ready-to-use molecular resource for the discovery of molecular pathways underlying susceptibility and resistance mechanisms of B. siamensis goniomphalos to O. viverrini and for comparative analyses with pulmonate snail intermediate hosts of other platyhelminths including schistosomes.